Fluorescence quenching of quantum dots by DNA nucleotides and amino acids1 - Siegberg, Daniel Wolfgang; Herten, Dirk-Peter (Australian journal of chemistry, 2011)
Quantum dots found widespread application in the biosciences as bright and highly photo-stable fluorescent probes, i.e. for single-particle tracking. In this work we used ensemble spectroscopy and single-molecule techniques to study the quenching of quantum dots by various biochemical compounds that are usually present in living cells and might thus influence the experiments. We found not only nucleotides such as cytosine, guanine, and thymine can significantly influence the fluorescence emission of CdSe and CdTe quantum dots, but also amino acids, like asparagine and tryptophan. Bulk studies on fluorescence quenching indicated a static quenching mechanism. Interestingly, we could also show by single-molecule fluorescence spectroscopy that quenching of the quantum dots can be irreversible, suggesting either a redox-reaction between quantum dot and quencher or strong binding of the quencher to the surface of the bio-conjugated quantum dots.